Whew, I made it! : The ABC’s of the first year as Chair – Transitions, Experiences and Strategies - Carolyn J Lee (Academic Chairpersons Conference Proceedings, 2020)
This presentation shares insights on the transition from faculty member to novice chair – a year of adjustments, challenges, rewards and lessons learned! Using literature findings and personal insight, the presenter will engage audience members to reflect on the value of their work and actively share in supportive dialogue.
Keywords: department chair; role transition; lessons learned; strategies; leadership